Hollywood ending : Harvey Weinstein and the culture of silence - Auletta, Ken (Penguin Press, 2022)
"A shocking account of how Harvey Weinstein rose to become one of the most iconic figures in the world of movies, how he used that position to feed his monstrous sexual appetites, and how it all came crashing down, from the author who has covered the Hollywood power game for the New Yorker for three decades. Twenty years ago, Ken Auletta wrote one of the iconic New Yorker profiles for which he is famous, of the Hollywood mogul Harvey Weinstein, then at the height of his powers. The profile created waves for exposing how volatile, even violent, Weinstein was to his employees and collaborators. But there was a much darker story that was just out of reach: rumors had long swirled that Weinstein was a sexual predator, but no one was willing to go on the record, and in the end he and the magazine concluded they couldn't close the case. But the story always nagged at him, and many years later, he was able to share his reporting notes and all that he knew with Ronan Farrow, and to cheer him along with Jodi Kantor and Megan Twohey as they broke their pioneering stories and wrote their bestselling books. But the story continued to nag at him. Farrow, Twohey, and Kantor did a brilliant job exposing the trail of assaults and their cover-up, but the larger questions remained: what explained Weinstein's monstrousness? Even more importantly, how and why was it never checked? How does a man run the day to day operations of a company with hundreds of employees and revenues in the hundreds of millions of dollars and at the same time live a shadow life of sexual predation without ever being caught, for years and years? How much is this a story about Harvey Weinstein, and how much is this a story about Hollywood and power? To answer that question fully, Ken Auletta has spent the past three years constructing a full reckoning with a career in film that has no parallel in Hollywood's history in its combination of extraordinary business and creative success and a personal brutality and viciousness that left a trail of ruined lives in its wake. How did one thing relate to the other? Hollywood Ending is an unflinching examination of Weinstein's life and career in full. Not simply a prosecutor's litany of crimes, it embeds them in the context of his overall business, his failures but also his outsized successes. To understand how he could behave as he did, we have to understand the power he wielded. Iconic film stars, Miramax employees and board members, old friends and family, even the person who knew him best, Harvey's brother Bob, all talked to Auletta at length. The result is not simply the portrait of a predator, it is a portrait of the power that allowed Weinstein to operate with such impunity for so many years, the spider web in which his victims found themselves trapped. To understand Weinstein's web is to understand how many other spider webs no doubt still remain."--